Empowering organizations through corporate social responsibility - Wolf, Ruth (Colección de libros electrónicos de ULoyola, 2014)
This book addresses the implementation of businesses' ethical standards in both emerging and advanced economies, interpreting the social impact of this issue in a global context by highlighting case studies, interdisciplinary perspectives, and strategies in business management